Port planning and management simulation - Wang, Wenyuan; Peng, Yun (Elsevier, 2022)
Port Planning and Management Simulation examines port planning simulation applications, showing how they supports better port decision-making. Using a clear organizational format based on actual port system structure and operation processes, the book provides practical and theoretical insights on port planning and management. The book describes the water, land, collecting and distributing components of the port system, focusing on management, development, and risk mitigation. It examines the key challenges based on discrete system simulation theory that is less affected by local or national regulations. It compares various simulation scenarios for optimal port operational strategy. It quantifies port emissions, analyzes the impact of different reduction strategies, and presents operational strategies for green port planning developmentmand management. Port Planning and Management Simulation provides guidance for carrying out deep analysis in a complex and dynamic system, providing an integrated solution framework based on simulation techniques for improving efficiency and cost savings of the port system.